Intersection of Personal and National History, 1985: (United States) - Schuman, Howard ([Verlag nicht ermittelbar], 1989)
These data explore the ways in which national and world events occurring over the past 50 years have affected respondents' lives and the lives of their families. A representative sample of Americans was queried about memories of important people, war-related issues including lessons learned from the Vietnam War, civil rights, and economic issues.